Service Recovery Strategy And Customer Satisfaction: Evidence From Hotel Industry In Yogyakarta-Indonesia - Budi Suprapto; Galang Yunanto Hashym (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2010)
This paper aims to discuss the findings from a study conducted concerning service recovery strategies and customer satisfaction among the hotels in Yogyakarta, Indonesia. The hospitality industry in Yogyakarta is a booming one and competition in the hotel industry is indeed stiff. To reduce the level of service failure in hotels as a result of unsatisfactory services, there is a need to identify recovery strategies to rectify and better manage the situation. The primary aim of this study is to analyze service recovery strategies and the impact of these strategies which consist of compensation, speed of recovery, and apology on service recovery satisfaction among hotel guests. A total of 113 respondents participated in this study comprising hotel guests in Yogyakarta, Indonesia by way of answering a set of questionnaire. Results from the regression analysis showed that compensation, speed of recovery, and apology are all influencing factors in customer satisfaction either implemented partially or wholly. Furthermore, it is indicated that apology has the biggest impact on customer service satisfaction compared to the other recovery strategies.